Hyperimmune Targeting Staphylococcal Toxins Effectively Protect Against USA 300 MRSA Infection in Mouse Bacteremia and Pneumonia Models - Han, Xiaobing; Ortines, Roger; Mukherjee, Ipsita; Kanipakala, Tulasikumari; Kort, Thomas; Sherchand, Shardulendra P.; Liao, Grant; Mednikov, Mark; Chenine, Agnes L.; Aman, M. Javad; Nykiforuk, Cory L.; Adhikari, Rajan P. (Frontiers in Immunology, 2022)
Staphylococcus aureus has been acquiring multiple drug resistance and evolved into superbugs such as Methicillin/Vancomycin-resistant S. aureus (MRSA/VRSA) and consequently is a major cause of nosocomial and community infections associated with high morbidity and mortality for which no FDA approved vaccines or biotherapeutics are available. Previous efforts targeting the surface-associated antigens have failed in clinical testing. Here, we generated hyperimmune products from sera in rabbits against six major S. aureus toxins targeted by an experimental vaccine (IBT-V02) and demonstrated significant efficacy for an anti-virulence passive immunization strategy. Extensive in-vitro binding and neutralizing titers were analyzed against six extracellular toxins from individual animal sera. All IBT-V02 immunized animals elicited the maximum immune response upon the first boost dose against all pore-forming vaccine components, while for superantigen (SAgs) components of the vaccine, 2nd and 3rd doses of a boost were needed to reach the plateau in binding and toxin neutralizing titers. Importantly, both anti-staphylococcus hyperimmune products consisting of full-length IgG (IBT-V02-IgG) purified from the pooled sera and de-speciated F(ab’)2 (IBT-V02-F(ab’)2) retained the binding and neutralizing titers against IBT-V02 target toxins. F(ab’)2 also exhibited cross-neutralization titers against three leukotoxins (HlgAB, HlgCB, and LukED) and four SAgs (SEC, SED, SEK, SEQ) which were not part of IBT-V02. F(ab’)2 also neutralized toxins in bacterial culture supernatant from major clinical strains of S. aureus. In-vivo efficacy data generated in bacteremia and pneumonia models using USA300 S. aureus strain demonstrated dose-dependent protection by F(ab’)2. These efficacy data confirmed the staphylococcal toxins as viable targets and support the further development effort of hyperimmune products as a potential adjunctive therapy for emergency uses against life-threatening S. aureus infections.